Meet Lina - Rippin, Sally (Penguin Books Australia, 2013)
It's 1956 and Lina dreams of being a writer, but her strict Italian parents have different ideas. Now that she's won a scholarship to an expensive girls school, Lina has other troubles, too. To fit in, she must keep her home life a secret, and her best friend Mary can't know the truth. But how long can Lina keep her two worlds apart?